1999
DOI: 10.1111/1467-9507.00092
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Structures, Social Information Processing, and Children’s Aggressive Behavior

Abstract: Although a multitude of factors may be involved in the development of children's violent behavior, the actual aggressive act is preceded by a decision-making process that serves as the proximal control mechanism. The primary goal of this longitudinal study was to understand the nature of this proximal control mechanism involved in children's aggressive acts by focusing on two aspects of social cognitions: social information processing and stored knowledge (i.e., internal knowledge structures that are the laten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(22 citation statements)
references
References 28 publications
1
18
0
3
Order By: Relevance
“…Nevertheless, some research suggests links between RS angry, external attributions for rejection, retribution and aggression. For example, (1) young people who tend to make external attributions for social failures are reported by others to be more aggressive (Guerra et al 2004), (2) child and adolescent beliefs about others as hostile is associated with more aggressive behavior (Burks et al 1999), (3) individuals who make external attributions for failure report more anger (Weiner and Graham 1984), and (4) aggressive children are more likely than withdrawn children to make other-blame attributions (Burgess et al 2006). These associations suggest that angry RS and blaming others for rejection would each be correlates of increasing aggressive behavior over time and that blaming others for rejection might also prompt even more angry expectations of rejection over time.…”
Section: Rs and Attributions For Rejectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, some research suggests links between RS angry, external attributions for rejection, retribution and aggression. For example, (1) young people who tend to make external attributions for social failures are reported by others to be more aggressive (Guerra et al 2004), (2) child and adolescent beliefs about others as hostile is associated with more aggressive behavior (Burks et al 1999), (3) individuals who make external attributions for failure report more anger (Weiner and Graham 1984), and (4) aggressive children are more likely than withdrawn children to make other-blame attributions (Burgess et al 2006). These associations suggest that angry RS and blaming others for rejection would each be correlates of increasing aggressive behavior over time and that blaming others for rejection might also prompt even more angry expectations of rejection over time.…”
Section: Rs and Attributions For Rejectionmentioning
confidence: 99%
“…Research has shown that adolescents' elevated depressive affect is linked to later isolation and withdrawal from social relationships (Nolen-Hoeksema et al 1986;Prinstein et al 2005). Also, other research has shown that adolescents with a history of aggressive behavior are more likely to respond with retribution and even more aggression when they are threatened by rejection (Burks et al 1999;Guerra et al 2004). These findings suggest that adolescents who report more depressive symptoms or aggression at T1 would report responding to rejection threat with withdrawal and retribution at T2, respectively, at the same time that T2 responses might be associated with later (T3) depressive symptoms and aggressive behavior with peers.…”
Section: Study Aims and Hypothesesmentioning
confidence: 99%
“…Researchers have noted that the way in which children interpret social events depends not only on aspects of online processing that occur when a child experiences social situations directly, but also their general representations about social interactions (e.g., Burks, Laird, Dodge, Pettit, & Bates, 1999), particularly in the context of ambiguous social events. For example, children who have been rebuffed by peers in the past may be more likely to assume that a hypothetical ambiguous behavior (e.g., a peer walking past another peer without saying hello) is intentionally negative.…”
mentioning
confidence: 99%
“…streiten viel -kommen gut miteinander zurecht), wurde bei den Jugendlichen die Tendenz erhoben, bei der Beschreibung von Personen auf feindliche Attribute zu fokussieren ("schema typicality"; SalzerBurks, Laird, & Dodge, 1999). Die Beschreibungen sollen kognitive Schemata für die Realität repräsentieren.…”
Section: Messinstrumenteunclassified
“…bei der Vorgabe eines Zieles generiert werden (Was würdest Du tun, um Dich hinsetzen zu können?) (nach Salzer-Burks et al, 1999). Die Fragen wurden im offenen Antwortformat erhoben, die Antworten anschließend kodiert.…”
Section: Messinstrumenteunclassified